Desenvolvimento do pensamento matemático: resolução de problemas de raciocínio lógico-matemático no Ensino Fundamental - Santos, José Ailton dos (2018)
This work has as main objective to contribute to the good performance of the student in solving math problems and logical reasoning. Many of our students have difficulties in solving math problems, and therefore have poor performance in reasoning correctly in logical terms. Concerned about this situation, the author of this work investigated the possible causes of these difficulties experienced in teaching practice and found bibliographical researches of mathematical educators such as Dante (2009), Isoda and Katagari (2012), Onuchic (1999), Onuchic and Allevato (2009) Polya (2006), Smole, Diniz and Candido (2000) eSpinilo (1994) that reveal why these people have difficulties in solving math problems and logical reasoning. We have also found that the development of logical reasoning is related to the ability to solve problems and that the insistent practice of exercises may not guarantee mathematical knowledge. With the objective of contributing to reduce the difficulties studied in the literature review, we did an experiment outside the classroom, test of sounding and presented suggestions of problems of logical reasoning to be applied in Elementary School.